COMMUNICATION SKILLS AS A KEY TO CAREER DEVELOPMENT IN THE DIGITAL AGE - Manohar, Palle; Reddy, G. Chenna (International Journal of Research -GRANTHAALAYAH, 2018)
The postmodern phenomenon of globalization has launched digitalization as an outcome and the part of communication technologies by which the world has been brought together transcending the barriers of countries and cultures. The increase of global trade and the necessity of close and interlinked association among the nations at various stages of development have become imperative today as a historical necessity for future survival. Communication skills, especially in English, have become a crucial ingredient in all most all activities of life as communication channels are the arteries through which information flows and circulates to sustain any activity without disruption. Besides, to that the growth of coordination and collaborative activities in all spheres of life both public and private. Acquisition of and master over communication skills are the intellectual tools by which one’s competence is measured and career is enhanced. In the age of specialization and hierarchal structures of large organizations, communication is the link connecting and synergizing all activities and ability to communicate clearly and effectively is of immeasurable significance, to assume an important place in any organization. Every field of activity has its own specific vocabulary, specialized jargon and modes of communication which should be mastered by all participants to maintain the overall activity, especially in the age of digitalization. To rise effectively in one’s career and contribute satisfactorily and successfully, special packages of communication skills should be designed and imparted to all potential candidates who are ambitious of to rise high in one’s career. The inauguration of digital age made it both convenient to choose ones place and time for learning and also challenging as to how to utilize the recent technologies to enhance and extend ones communicative reach to become successful in one’s career. The purpose of this paper is to discuss the various programs and strategies of communication necessary to enhance ones career prospects by training the participants to equip themselves with right competitive communication skills in tandem with contemporary digital technology available.